Extensive ossifications of falx cerebri - literature review based on own experience and case report - Zygmunt Siedlecki; Bartłomiej Gromadzki; Jakub Woźniak; Kalina Jagodzińska; Kajetan Hadzik; Maciej Śniegocki (Kazimierz Wielki University, 2020)
Extensive ossification of the falx cerebri occur rarely however are described in the world literature references. Ossifications may concern both cerebral falx and other dural structures: tentorium. They are most often incidental findings and occurrence frequency in the population is remains unclear. The authors of the study are reviewing references on this subject, based on a case of extensive falx ossification. Manuscript describes the case of incidental detected of extensive calcification of the anterior brain sickle in a patient after head injury. Computed tomography revealed no pathology, but extensive ossification of falx was described. The patient did not complain of any significant complaints or neurological symptoms. The described calcification constituted a median and sagittal bone or calcium plate separating the frontal lobes of the brain. Analyzing references did not identify such extensive ossification of falx cerebri in human, however dural ossifications are reported in the references.